Correlation between Hyperglycemia Stress and Short-Term Memory Function in Thrombotic Stroke Patients - Muhammad Hamdan1, Riani Wisnujono1, Yudha Haryono1, Abdulloh Machin1, Dian Puspitarini1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Hyperglycemic stress is associated with a disorder of the entire cognitive domain in the early phase of stroke, which is memory impairment. Acute changes in blood glucose are known to affect the cerebral blood flow. Objectives: To determine the relationship between stress hyperglycemia with short-term memory function in thrombotic stroke patients. Method: An observational analytic research with the case-control with a patient’s of 72-hour onset thrombotic stroke that went to the Emergency Unit and was admitted to the Neurology Department of Dr. Soetomo General Hospital from January to December 2014. 42 subjects were enrolled (21 subjects in the case group and 21 subjects in the control group). The sampling of the study was conducted according to the cases that came in succession until the achievement of the subject was determined. Results: After bivariate and multivariate analysis, hyperglycemic stress had no significant correlation to memory function (p = 0.525) and OR 0.667 (CI95% = 0.190-2.334). There was a significant correlation between educational level and cognitive function (p = 0.003) also between hypertension and cognitive function (p = 0.019). Conclusion: Stress Hyperglycaemia has no significant relationship with memory function. Education levels and hypertension have a significant correlation with memory function.